Pandemic preparedness and management in European out-of-hours primary care services - a descriptive study - Ingrid Keilegavlen Rebnord; Guri Rortveit; Linda Huibers; Jonas Nordvik Dale; Marleen Smits; Tone Morken (BMC, 2023)
Abstract Background Primary care is the first point of contact for all acute health problems. As such, primary care was at the frontline in the COVID-19 pandemic, playing a significant role in clinical responses and information to the public. This study aimed to describe the variations in patient management strategies used in the out-of-hours services in different European countries during the first phase of the pandemic. Method We conducted a cross-sectional web-based survey in August 2020, selecting key informants from European countries using European networks. The questionnaire was developed in collaboration with researchers in the field of out-of-hours primary care. We performed descriptive analyses per region, structuring results into themes. Results Key informants from 38 regions in 20 European countries responded. Seven regions reported that their out-of-hours services had a pandemic preparedness plan, three had trained on the plan, and two had stockpiles of personal protection equipment before the outbreak. Extension of telephone triage lines and establishment of local infection-control teams and clinics were the main patient management strategies. Other strategies for patient contacts were also used in the regions, such as video-consultations (13 regions), electronic consultations (21 regions), patient's car as alternative waiting room (19 regions), outside tents for testing (24 regions), "drive-through" testing (26 regions), and separate departments for infected patients (14 regions). Conclusion Few out-of-hours services were well prepared for a pandemic, but all expanded and reorganized rapidly, adopting new strategies for patient management and treatment. The results could be useful for planning of organization preparedness of out-of-hours primary care service for future pandemics.